Effects of shrinkage, temperature and the degree of connection (N/Nf) on the behavior of steel-concrete composite beams - Aouad, Halima; Rahal, Nacer; Beghdad, Houda; Sadoun, Mohamed; Souici, Abdelaziz; Zatir, Sara; Benmahdi, Khaled (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Temperature and time-dependent effects such as concrete shrinkage and creep significantly affect the behavior of steel-concrete composite beams. Hence, taking into account the demands brought by these additional effects is necessary. This necessity has resulted in various theoretical and numerical research studies. This article proposes an analytical tool capable of predicting a new redistribution of stresses brought by the combined action of temperature and concrete shrinkage in composite steel-concrete beams in partial shear connection. In this work, the partial shear connection at the steel-concrete interface is taken into account according to the degree of connection (N/Nf)     Methods: This involves reformulating the model proposed in 2024 by Rahal et al analyzing the behavior of composite steel-concrete beams in full shear connection under the effect of temperature and concrete shrinkage. In this present study, the main contribution is the introduction of the effect of the connection degree (N/Nf) at the steel-concrete interface, thus leading to an analytical model capable of predicting additional stresses brought by shrinkage and temperature in composite steel-concrete beams in partial shear connection.Results: When referred to the model proposed in 2024 by Rahal et al, the results from this current approach are satisfactory. They clearly show that the degree of connection significantly affects the forces brought about by the combined action of concrete shrinkage and temperature.Conclusion: The results of the present approach and those of the existing model developed by Rahal et al are in good agreement. They clearly show the effect of concrete shrinkage and temperature as a function of the connection degree N/Nf on the behavior of composite steel-concrete beams.
Keywords: degree of connection (N/Nf); shrinkage; time; steel-concrete interface